Land subsidence and its affecting factors in Cangzhou, North China Plain - Guo, Haipeng; Hao, Aibing; Li, Wenpeng; Zang, Xisheng; Wang, Yunlong; Zhu, Juyan; Wang, Liya; Chen, Ye (Frontiers in Environmental Science, 2022)
Land subsidence is a typical geo-hazard in Cangzhou, North China Plain, having caused severe damages to transportation networks, public utilities, and other civil infrastructures. The mechanism of land subsidence and its affecting factors were revealed by theoretical model analysis, and doing geotechnical tests and monitoring of soil deformation as well as groundwater level. Theoretical analysis shows that groundwater withdrawal from both unconfined and confined aquifers can lead to land subsidence. Land subsidence of the Cangzhou Plain is mainly caused by the exploitation of deep confined groundwater. Geotechnical tests show a general trend that the compressive modulus increases with the increase of soil depth. The strata of the Upper Pleistocene and Holocene are mostly normally consolidated and partially under-consolidated, which are prone to produce large compression after pumping. Land subsidence in the Cangzhou Plain has a strong hysteresis because of seepage consolidation and creep. The deformation characteristics of strata change at different depth. The shallow aquifers are mainly elastic deformation. The area of severe land subsidence in the Cangzhou Plain is closely related to rainfall, mainly because the large amount of water are used for agricultural irrigation. InSAR results show a sudden change in regional subsidence across the Cangdong fault, which is caused by the difference in the thickness of Quaternary sediments and the difference in the deep confined groundwater level.